2018
DOI: 10.1136/postgradmedj-2018-135602
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillar microbiome: an update

Abstract: Pathogenic bacteria associated with the adenoids and tonsils cause much morbidity in the paediatric population. Hyperplasia of the adenoids is associated with otitis media with effusion and hyperplasia of the palatine tonsils is associated with both recurrent tonsillitis and obstructive sleep apnoea. Most current knowledge of the microbiology of the upper airways has been derived from culture-based studies, which usually reflect only a small fraction of the bacteria present on the mucosal surface. Culture-inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…Many studies have shown that the tonsils of patients with recurrent tonsillitis are colonized by a large number of bacteria, both pathogenic and nonpathogenic, showing that these agents possibly may play a role in the development of chronic tonsillar disease [ 1 , 7 , 21 , 25 ]. In patients undergoing adenoidectomy, for instance, there is a decrease in the detection of pathogenic agents in the nasopharyngeal region [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the tonsils of patients with recurrent tonsillitis are colonized by a large number of bacteria, both pathogenic and nonpathogenic, showing that these agents possibly may play a role in the development of chronic tonsillar disease [ 1 , 7 , 21 , 25 ]. In patients undergoing adenoidectomy, for instance, there is a decrease in the detection of pathogenic agents in the nasopharyngeal region [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, according to some hypotheses, such symptoms are linked to the neuronal cells’ impairment or to ischemic harm of the central nervous system, but also to an increase in Interleukin-6 [ 38 , 39 , 40 , 41 , 42 ]. Otitis is an acute infection of the middle ear and occurs most often in children and it is mainly due to Pneumococcus , Haemophilus and Staphylococcus [ 5 , 22 , 43 ]. Several factors can increase or decrease the risk of appearance of a lung disease.…”
Section: Pathogenesis Of Respiratory Disordersmentioning
confidence: 99%
“…The pathophysiology of recurrent tonsillitis in children has focussed on the microbiome of the pharynx. Cultivation studies have demonstrated numerous pathogenic bacteria in the pharynx in asymptomatic children and in those with recurrent tonsillitis [ 6 ]. Similar studies have demonstrated latent viral reservoirs which also may play a role.…”
Section: Introductionmentioning
confidence: 99%